2016
DOI: 10.1613/jair.5153
|View full text |Cite
|
Sign up to set email alerts
|

Goal Probability Analysis in Probabilistic Planning: Exploring and Enhancing the State of the Art

Abstract: Unavoidable dead-ends are common in many probabilistic planning problems, e.g. when actions may fail or when operating under resource constraints. An important objective in such settings is MaxProb, determining the maximal probability with which the goal can be reached, and a policy achieving that probability. Yet algorithms for MaxProb probabilistic planning are severely underexplored, to the extent that there is scant evidence of what the empirical state of the art actually is. We close this gap with a compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…Planning algorithms aim to find strategies which perform well (or even optimally) for a given objective. These algorithms typically assume that a goal is reached eventually [41,45]. This however is unrealistic in many scenarios, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Planning algorithms aim to find strategies which perform well (or even optimally) for a given objective. These algorithms typically assume that a goal is reached eventually [41,45]. This however is unrealistic in many scenarios, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In [27], three different model checking approaches are explored and compared. A survey for heuristic approaches is given in [45]. A Q-learning based approach is described in [13].…”
Section: Introductionmentioning
confidence: 99%
“…Symbolic implementations of the iterative algorithms should also be tested in practice. In a more theoretical direction, we observe that the planning community has also studied maximizing the probability of reaching a target set of states under the name of MAXPROB (see, e.g., [17,22]). There, online approximations of the NWR would make more sense than the under-approximation we have proposed here.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, it is EXPTIME-complete to find such an optimal policy in general [28]. Furthermore, recent experiments have shown that, even with very specific restrictions on the action model, finding an optimal policy for a penetration testing task is feasible only for small networks of up to 25 hosts [43]. For the sake of scalability and following the lines of Stackelberg Planning [42], we thus focus on finding critical attack paths, instead of entire policies.…”
Section: Mitigation Analysis As Stackelberg Planningmentioning
confidence: 99%